An Optimization of Language Learning in Writing Through E-Learning: Encountering Covid-19 Pandemic - Sariani, Sariani; Khairat, Mutia El; Yaningsih, - (Universitas Negeri Makassar, 2021)
In response to the current situation of the pandemic covid-19 outbreak which has been affected worldwide, this study examines the opt on online learning for writing skill, and to assess the development of the writing task. It draws the data from an English as a Foreign Language (EFL) studentâ€™s writing documents, and marking documents of three experienced English teachersâ€™s using the â€œAnalytical Marking Schemeâ€. A qualitative approach was employed where the data was obtained during the online supervision of the studentâ€™s final project (TA) by integrating visual images into her writing project. The participant is in her final year at English Department, Politeknik Negeri Padang who focuses on writing brochure as her TA. The findings of this study show that there are two major progresses found in the writing documents of the first draft to the final draft. First, the content of the writing has been improved as seen from the variation of vocabulary used within. The essay has been organized well where the ideas are developed, and the information shared is logical and complete. Second, even though there is still a few errors occured in grammar, punctuation, and spelling, they have no influence on the idea conveyed. The student is able to adjust into the online learning, and increase her writing performance by utilizing the visual images given. The findings suggest that there should be more innovative learning designs to accommodate the needs of online learning. Since this type of learning is challenging for both teachers and student, teachers need to be able to put their role as facilitator to establish more engagements with the student, and to trigger the student to be more autonomous in learning.Â